CWDM for Aerospace Applications - Temperature Testing of COTS Technologies - White, H.J.; Watson, M.A.; Proudley, G.M.; Proudfoot, A.; Aldridge, N.B. (2007 IEEE Avionics, Fiber-optics, and Photonics Technology Conference : Victoria, BC, Canada, 2-5 October 2007, 2007)
Coarse wavelength-division multiplexing (CWDM) systems offer significant advantages over the more conventional dense wavelength-division multiplexing (DWDM) networks for aerospace applications. In DWDM, the spacing between adjacent channels is typically <1nm, whereas the CWDM standard is 20nm channel spacing. By exploiting this WDM standard, the requirement for an optical source to transmit at a specific, well-defined wavelength is somewhat relaxed, enabling a degree of centre wavelength drift with temperature to be tolerated -the CWDM standard defines a 13nm filter bandwidth. This promises significant reductions in device cost, weight, volume and power consumption, since it may be possible to use un-cooled laser sources. However, this assumes that the CWDM filter technology is stable over the aerospace operating conditions. This paper looks at both source and filter CWDM devices and in particular their performance over the airframe (-55 to +125degC) and avionic (-40 to +85degC) temperature ranges. CWDM filters from two different COTS providers were studied, as well as several different commercial CWDM transceivers. In all cases the devices were at times subject to temperatures beyond those specified by the manufacturers.